تمثلات الفضاء المديني وتحولاته في رواية أشباح المدينة المقتولة لبشير مفتي - متلف, آسيا (University of El-oued, 2020)
شكّلت المدينة في الرواية العربية موضوعا خصبا لا يستهان به ،إذ استطاعت أن تطرق عالمه بمختلف ملامحه وصوره فقد كان لها حضور متميز في مجموعة من النصوص الروائية الجزائرية التي سعت الى نقل مجموعة من التحولات التي عرفها المجتمع الجزائري خاصة في فترة ما بعد الاستقلال، إذ حاول الروائيون الجزائريون رصد تحولات الحركة الاجتماعية والسياسية وانعكاساتها على الفرد من خلال توظيف الفضاء المديني بشكل فني متميز، يدل على اتساع ثقافة هؤلاء وعمق تفكيرهم، ونذكر على سبيل المثال لا الحصر الروائي "بشير مفتي"، الذّي صور لنا مدينة الجزائر العاصمة وتحولاتها في فترة حاسمة من تاريخ الجزائر في رواية "أشباح المدينة المقتولة" تصورا عميقا متشعب الأبعاد يتراوح بين الديني والتاريخي والثقافي وكذا السياسي، فقد شكّل هذا الفضاء داخل الرواية خصوصية فنية ذات بعد إنفعالي نتيجة تداخل المادي والمعنوي وتميّز هذا الفضاء_حي مارشي بالجزائر العاصمة_كفضاء يحمل مجموعة من الترسبات والتراكمات التراثية الغارقة في الذاكرة . وحري بنا أن نتساءل في هذا السياق عن تجليات صورة المدينة وتحولاتها باعتبارها مسرحا للأحداث السياسية و الاجتماعية والفكرية من خلال تيمة العنف داخل الرواية، وهل استطاع بشير مفتي من خلال توظيفه للفضاء المديني أن ينقل وعيا ابداعيا شديد الخصوصية بالمكان عموما وبالمدينة بصفة خاصة ؟ The city has been a fertile theme in the Arabic novel. It has been able to address its world in all its features and images. It had a particular presence in a collection of Algerian narrations that sought to convey a series of transformations that Algerian society had known especially after independence. Algerian novelists focused more on the transformations of the social and political movement, examining its impact on the individual through the use of urban space in a distinct technical manner. That indicates their deep intellectuality. For instance, "Bashir Mufti," one of those Algerian novelists, portrayed the city of Algiers, reflecting its transformations in a crucial period, through his novel, “The Ghosts of the Murdered City”. He depicted the city deeply, in multidimensional views: religious, historical, cultural and political. This space has created an artistic dimension with an emotional dimension as a result of the physical and moral overlap. This space which is Marchi in Algiers is characterized by a combination of sediments and accumulated heritage in the memory. In this context, this study aims at examining the manifestations of the image of the city and its transformations as a theater of political, social and intellectual events through the theme of violence within the novel. So, could Bashir Mufti, through his employment of urban space, convey a very creative awareness of the place in general and the city in particular?
مقال. مجلة القارئ للدراسات الأدبية والنقدية. مج03. ع.02. جامعة الوادي
Keywords: تمثلات، تحولات، فضاء، المدينة